2006
DOI: 10.1007/s10570-005-9045-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel cellulose fibre reinforced thermoplastic materials

Abstract: Spun cellulose fibres from the viscose, lyocell and carbamate processes have been used to reinforce thermoplastic commodity polymers, such as polypropylene (PP), polyethylene (PE) and (high impact) polystyrene (HIPS) as well as poly(lactic acid) (PLA) and a thermoplastic elastomer (TPE) for injection moulding applications. A specially developed double pultrusion technique has been employed for compounding. Fibres were analysed in single fibre tensile tests. Strength, stiffness, impact strength, and heat distor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(95 citation statements)
references
References 10 publications
2
90
0
3
Order By: Relevance
“…According to Ganster and Fink fineness of Cordenka fibre is 0.18 tex, strength is 56±4 7 cN/tex (833 N/mm²), elongation is 13±2 %, and Young´s modulus is 1300 cN/tex (20 8 GPa) [14]. 800 g/m².…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Ganster and Fink fineness of Cordenka fibre is 0.18 tex, strength is 56±4 7 cN/tex (833 N/mm²), elongation is 13±2 %, and Young´s modulus is 1300 cN/tex (20 8 GPa) [14]. 800 g/m².…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…But PLA has become an important part of R&D in the recent years because 11 of the benefits listed above. Mechanical tests on natural fibre reinforced PLA have been 12 performed with different types of fibres like kenaf [9, 10], jute [11], flax [12] abaca 13 [13], hemp [7] and Cordenka rayon fibres [14]. MPa, a Young's modulus of 3.11 GPa and an impact strength of 16.13 kJ/m 2 was 15 measured for this material in a former publication [7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is known that an important increase in strength and stiffness of polymer matrix can be obtained at concentrations above 30% of micron sized cellulose fibers, lower concentration of 20 -25% being effective only in the case of a good treatment of fibers or coupling agent adding. In these composites, elongation at break knows significant decreases, polymer matrix ductility being severely altered by micron sized fibers (Bledzki et al, 2003;Ganster et al, 2006). Hence, it was not expected that the low concentration of L fibers could improve PVA mechanical properties.…”
Section: Cellulose Fibers Characterizationmentioning
confidence: 99%
“…Regenerated cellulose fibers are chemically pure, their surface structure is even, and the fiber properties can be reproduced easily (Woodings 2001;Carrillo et al 2010;Adusumali et al 2006;Fink et al 2014). It is also found that these fibers have good potential to be used as reinforcement in FRC (Carrillo et al 2010;Adusumali et al 2006;Ganster and Fink 2006;Jaturapiree et al 2006). High surface evenness and even quality of these fibers makes it possible to get consistent results which are not possible in natural fiber (Woodings 2001).…”
Section: Introductionmentioning
confidence: 99%